Chains, trains and automobiles: Medical transport for prisoners in Switzerland - Haesen, Sophie (European journal of criminology, 2023)
Imprisoned persons are transported for several purposes including transfers to a different prison, legal-procedural reasons such as court hearings, and to receive medical treatments. The availability and acceptability of transportation may limit access to healthcare if health services cannot be provided within the prison grounds. The aim of this article is to examine the conditions of medical transport for older prisoners in Switzerland and to assess whether or not these practices are in line with international recommendations. Interviews with experts working in the prison context and with older prisoners were conducted. Results show that handcuffing practices and space restrictions during medical transport are not adapted to prisoners? health condition. Older prisoners risk being exposed and humiliated by transport conditions. The reasons for delayed medical transport can be administrative constraints or erroneous medical judgement. Switzerland?s cantonal system results in a variety of regulations for transports, so that cantonal differences, administrative constraints and inappropriate conditions can delay access to necessary healthcare and increase suffering.